OCCULT HEPATITIS B VIRUS INFECTION AND ASSOCIATED GENOTYPES AMONG HBSAG-NEGATIVE SUBJECTS IN BURKINA FASO - Birama DIARRA; Albert Théophane YONLI; Pegdwendé Abel SORGHO; Tegwinde rebecca COMPAORE; Dorcas Obiri -Yeboah; Abdoul Karim OUATTARA; Traore Lassina; Wendpagnangdé Arsène ZONGO; Serge Théophile Soubeiga; Virginio Pietra; Bolni-Marius Nagalo; Wendkuuni Florencia Djigma; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Occult Hepatitis B virus infection (OBI), is characterized by the absence of detectable HBsAg in the blood of a person assumed to be healthy. It remains a potential transmission threat and risk to HBV chronic infection. The purpose of this study was to determine the OBI prevalence among HBsAg negative subjects and to characterize associated genotypes.